2016
DOI: 10.1002/anie.201608780
|View full text |Cite
|
Sign up to set email alerts
|

H2S Sensors: Fumarate‐Based fcu‐MOF Thin Film Grown on a Capacitive Interdigitated Electrode

Abstract: Herein we report the fabrication of an advanced sensor for the detection of hydrogen sulfide (H S) at room temperature, using thin films of rare-earth metal (RE)-based metal-organic framework (MOF) with underlying fcu topology. This unique MOF-based sensor is made via the in situ growth of fumarate-based fcu-MOF (fum-fcu-MOF) thin film on a capacitive interdigitated electrode. The sensor showed a remarkable detection sensitivity for H S at concentrations down to 100 ppb, with the lower detection limit around 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
157
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(158 citation statements)
references
References 34 publications
1
157
0
Order By: Relevance
“…The response values (ΔR/R 0 ) of NO 2 sensors reported in recent literatures are illustrated in Figure 4f, and the detailed sensing properties are summarized in Table S2 in the Supporting Information. [49][50][51][52][53][54][55][56] Although the response of Pd@Cu 3 (HHTP) 2 was slightly lower than those of other materials, a significant improvement in MOF-based sensors has been achieved in this work by combining the metal NPs with C-MOFs. The Pd@ Cu 3 (HHTP) 2 exhibited the highest NO 2 response among MOFbased sensors reported to date, including MOFs, C-MOFs, and MOF derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…The response values (ΔR/R 0 ) of NO 2 sensors reported in recent literatures are illustrated in Figure 4f, and the detailed sensing properties are summarized in Table S2 in the Supporting Information. [49][50][51][52][53][54][55][56] Although the response of Pd@Cu 3 (HHTP) 2 was slightly lower than those of other materials, a significant improvement in MOF-based sensors has been achieved in this work by combining the metal NPs with C-MOFs. The Pd@ Cu 3 (HHTP) 2 exhibited the highest NO 2 response among MOFbased sensors reported to date, including MOFs, C-MOFs, and MOF derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…[49] For example,H 2 S, aw ell-known gasotransmitter is known to play a important role in various pathological and physiological processesi nv arious organisms.A ni ncrease in the level of H 2 Sc an lead to Alzheimer's disease, diabetes, Down's syndrome, and cancer.K eeping this in mind variousg roups have come up with MOF based H 2 Ss ensors which can detect trace amounts. [50] In 2014, Ghosh and co-workers reportedaMOF based turnon fluorescence probe for selectived etection of H 2 Sg as. They synthesized the MOF "1-NH 2 "b yasolvo-thermal reactiono f2aminoterephtalic acid and ZrCl 4 and subsequently by treating 1-NH 2 with NaN 3 ,t hey gott he desired azide-functionalized post-synthetically modifiedM OF 1-N 3 which shows selective turn-onf luorescencer esponse towards H 2 S ( Figure 11).…”
Section: Sensing Of Bio-markersa Nd Biologically Active Compoundsmentioning
confidence: 99%
“…Meanwhile, we also studied the effect of H 2 S concentration for the fluorescent test paper. As shown in Figure S19 (Supporting Information), the lightened degree of the fluorescent test paper increases with the concentration increase of H 2 S gas, and the LOD is lower than 30 ppb, which was lower than many other reported sensors for detecting H 2 S. [49,50] All the results suggested that the Zr(TBAPy) 5 (TCPP)-based fluorescent test paper can high selectively and sensitively detect H 2 S gas in real-time.…”
Section: Metal Organic Frameworkmentioning
confidence: 99%